A study on the viability of SEM-Calaca coal bottom ash as partial fine aggregate replacement in the development of self-compacting concrete - Del Rosario, Carl Anthony M.; Diola, Nathaniel B.; Germar, Fernando J.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Civil engineering practices at present are aimed at the efficient use of resources. The pressing issue of waste and disposal pushes the need for sustainable efforts in the construction sector. This paper is a critical review on the feasibility of coal bottom ash (CBA) as partial replacement for fine aggregate in self-compacting concrete (SCC). Coal bottom ash is believed to be a viable raw material for concrete, therefore, an exhaustive approach is needed to determine its behavior. As prerequisite, the engineering properties of bottom ash are determined through standard methods imposed by the American Society for Testing and Materials (ASTM). An initial trial mix following the recommendations of the Japan Society of Civil Engineers (JSCE) and the American Concrete Institute (ACI) is determined: Fresh concrete tests conforming to standard criteria such as Slump Flow Test, V-Funnel Test, L-box Test, and U-Flow Test are used to determine the acceptable SCC mix. Concrete samples are then proportioned according to varying degrees of bottom ash replacement (0%, 10%, 20%, 30%, 40%). Accepted concrete mixes are poured over lubricated 4" x 8" cylindrical molds and are allowed to cure for 1, 7, and 28 days after a 24-hour setting period. Non-destructive tests followed by the ultimate compressive test are conducted using the hardened concrete mix. From the study, it was discovered that the workability of the experimental SCC mix decreases with the increase of bottom ash replacement at a fixed water-powder ratio. The structure of bottom ash particles in addition to the water-reducing effect of the superplasticizer inhibits the flow characteristics of concrete. Variability of flow values can be attributed with the time of sampling. Early strength of SCC containing bottom ash is lower than that of the control mix due to delays in hydration of concrete. At later ages of curing, the experimental mixes gained a significant increase in compressive strength, associated with the reduction of free water as well as the interlocking of bottom ash particles. The 7-day compressive strength of SCC with 10%, 20%, and 30% replacement surpassed the 28-day compressive strength of the control mix. From this, an optimum bottom ash replacement of 20% is recommended to produce a SCC mix with considerable workability and strength properties. Such properties are applicable to deep structures such as walls and columns of low-rise to medium-rise buildings. Ultimately, the study confirmed the feasibility of bottom ash-incorporated self compacting concrete in the Philippines -- a step to an economically and environmentally fruitful future for construction practices in the country.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Coal ash; Self-consolidating concrete; Fly ash; Coal-fired power plants; Superplasticizers; Rheological properties